KEADILAN ORGANISASI DAN UPAYA MEWUJUDKAN KEPUASAN KERJA KARYAWAN - Mukti Kemarauwana; Didit Darmawan (Jurnal Ilmiah Satyagraha, 2023)
Organizational management has an important task so that the company's operations can continue to run. Management of employees as company assets becomes part of management. Company management tries not to lose its employees by increasing job satisfaction. Various factors that can increase job satisfaction are researched and developed. This study aims to determine the role of distributive justice and procedural justice to be able to develop job satisfaction. This quantitative research was conducted in one of the business entities operating in Malang City. This study uses the census method as a sample of 60 employees who work. Research data obtained through questionnaire responses. Data were analyzed by multiple linear regression. The data processing process proves that distributive justice has a significant influence on the development of job satisfaction. Research also proves that procedural justice plays a significant role in shaping employee job satisfaction. Together, distributive justice and procedural justice have a significant impact on increasing job satisfaction.